2007
DOI: 10.1111/j.1439-0507.2007.01394.x
|View full text |Cite
|
Sign up to set email alerts
|

Candida lusitaniae arthritis in an intravenous drug user

Abstract: A case of arthritis of the right knee caused by Candida lusitaniae in a 29-year-old intravenous drug abuser is described. The diagnosis was based on the isolation of C. lusitaniae from synovial fluid and was supported by the presence of C. lusitaniae-specific DNA and high levels of (1-3)-beta-d-glucan (122 pg ml-1) in the same specimen. While the isolate was susceptible to amphotericin B and fluconazole in vitro, treatment with amphotericin B was not very effective. The patient achieved complete cure with fluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Limited data suggest that positive predictive values of β-D-glucan in bronchoalveolar lavage fluid are poor for diagnosing fungal pneumonia [159]. There are case reports for testing of samples collected from other sites of invasive Candida infection [160].…”
Section: Antigen and Antibody Detectionmentioning
confidence: 99%
“…Limited data suggest that positive predictive values of β-D-glucan in bronchoalveolar lavage fluid are poor for diagnosing fungal pneumonia [159]. There are case reports for testing of samples collected from other sites of invasive Candida infection [160].…”
Section: Antigen and Antibody Detectionmentioning
confidence: 99%
“…In a recent case report of a patient with Candida lusitaniae joint infection, beta-glucan testing demonstrated high concentrations corresponding to the positive cultures. 28 Studies in rabbits infected with Candida albicans to create an experimental model for hematogenous candidal meningoencephalitis found that 100% of the animals had demonstratable levels of beta-glucan in the cerebrospinal fluid. 29 In animals cleared of the infection, levels of betaglucan in the cerebrospinal fluid decreased as a marker for response to therapy.…”
Section: Therapeutic Monitoringmentioning
confidence: 99%
“…In Kuwait, little information is available on the association of C . lusitaniae with human colonization and infection [14]. This study describes prevalence and susceptibility profile of clinical isolates of C .…”
Section: Introductionmentioning
confidence: 99%